2018
DOI: 10.3390/su10041298
|View full text |Cite
|
Sign up to set email alerts
|

Walled Buildings, Sustainability, and Housing Prices: An Artificial Neural Network Approach

Abstract: Various researchers have explored the adverse effects of walled buildings on human health. However, few of them have examined the relationship between walled buildings and private housing estates in Hong Kong. This study endeavors to fill the research gap by exploring the connections among walled-building effects, housing features, macroeconomic factors, and housing prices in private housing estates. Specifically, it reveals the relationship between walled buildings and housing prices. Eight privately owned ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 34 publications
(51 reference statements)
1
26
0
Order By: Relevance
“…Thus, more skyscrapers are being constructed following a "build up, not out" approach [5]. Moreover, the policy regarding the extra gross floor area offers developers bonuses and exemptions for green feature provisions, which have become powerful motivations for developers to increase both the number of floors and the mass of buildings [6]; as a result, Hong Kong has the largest number of tall buildings above 150 metres worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, more skyscrapers are being constructed following a "build up, not out" approach [5]. Moreover, the policy regarding the extra gross floor area offers developers bonuses and exemptions for green feature provisions, which have become powerful motivations for developers to increase both the number of floors and the mass of buildings [6]; as a result, Hong Kong has the largest number of tall buildings above 150 metres worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…With regard to the research into demographic factors, the existing literature has focused on the demographic age structure [41- With the booming development of the real-estate market and the rapid growth of housing prices, the factors influencing housing prices have attracted wide attention from scholars at home and abroad. Focused on the factors affecting housing prices, the existing research has achieved very fruitful results, including in macroeconomics (real-estate investment [9], economic growth [10,11], monetary policy [12,13] and inflation [14]), politics (urban hierarchy [15] and government policy [8]), society (population factors [16,17], social environment [18] and urbanization [19,20]), physical geography (geographical location [21], natural features [22] and environmental health risks [23,24]) and micro-aspects of real-estate characteristics (walled buildings [25], cost of construction and installation [26,27], house type [28,29], locational conditions [30], educational resources [31], infrastructure [32][33][34] and neighborhood factors [35,36]), and the household and individual characteristics of household buyers (income [37,38], the Dutch index of consumer confidence [39] and consumer expectations [40]). As the main subject of investing, consuming, using and disposing of real estate, the human factor has gradually become the research focus.…”
Section: Introductionmentioning
confidence: 99%
“…In Hong Kong, high-density urban forms reduce urban air ventilation (Ng, 2009 ), and the environmental challenges it brings include, but not limited to, urban heat island effects (Shi et al, 2018a , 2018b ), prolonged extreme hot weather (Cai et al, 2017 ; Shi et al, 2019 ), and deteriorated outdoor air quality and microclimate condition (Shi et al, 2016 ). Building morphological forms have been found to be influential to housing price in Hong Kong (Li et al, 2018 ). It has been found that concerns about climatic risks also affect the urban real estate market (Bunten & Kahn, 2014 ).…”
Section: Literature Reviewmentioning
confidence: 99%